Etiology and Symptomatics of Dyspepsia in Lambs (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The article provides an analysis of the results of scientific research aimed at determining the etiology and clinical signs of dyspepsia in lambs in different geographical zones of Uzbekistan.